Implementation of Public Policy in Encouraging the National Digital Economy: Perspectives of Indonesian MSME Actors - Amelia, Amelia (GEMA EKONOMI, 2024)
Digital transformation is one of the public policy priorities in Indonesia with the main goal of encouraging MSMEs to enter the digital economy ecosystem. However, the effectiveness of the implementation of this policy still faces challenges in literacy, infrastructure, and business sustainability. This study aims to analyze the perception of MSME actors towards the implementation of public policies in encouraging the national digital economy, identify the obstacles faced, and explore the adaptation strategies carried out. Using a descriptive qualitative approach, this study involved 100 MSME actors from various sectors through in-depth interviews, observations, and study of policy documents. The data was analyzed with NVivo 12 Plus's software-assisted thematic analysis techniques to find key patterns and themes. The results of the study show that most MSME actors feel the benefits of policies in the form of increased market access and promotion efficiency, but there are still significant obstacles in the form of low digital literacy, limited internet infrastructure, high logistics costs, and low access to training. These findings confirm the gap between policy formulation and the reality of implementation on the ground. This research contributes to the literature by presenting a direct perspective of MSME actors, as well as providing practical implications for governments to strengthen human resource capacity, expand digital infrastructure, and design more inclusive logistics regulations.